2019
DOI: 10.31857/s0869-56524863297-300
|View full text |Cite
|
Sign up to set email alerts
|

The production of pure hydrogen peroxide solutions in water activated by plasma of the electrodeless microwave discharge and their application to control plant growth

Abstract: Поступило 20.12.2018 г.Разработан метод получения чистых растворов пероксида водорода при активации воды плазмой безэлектродного СВЧ-разряда. Показано, что активированная вода обладает выраженным действием на сельскохозяйственные растения, являясь нетоксичным и химически чистым регулятором биологической активности. В частности, с помощью обработки семян сельскохозяйственных растений растворами активированной воды можно повысить их засухоустойчивость.Ключевые слова: пероксид водорода, СВЧ-разряд, активированная… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…It was found that under conditions of water shortage when treating with plasma-activated water, the germination of Vigna mungo L. seeds increased by 10–15% [ 40 ]. Andreev et al showed that plasma-activated water in laboratory conditions could improve the drought tolerance of seeds (10–20%) of radish [ 41 ], wheat [ 42 ], and other crops, as well as increase the rate of seed germination under drought conditions. A number of other laboratory examples are provided in the review article [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that under conditions of water shortage when treating with plasma-activated water, the germination of Vigna mungo L. seeds increased by 10–15% [ 40 ]. Andreev et al showed that plasma-activated water in laboratory conditions could improve the drought tolerance of seeds (10–20%) of radish [ 41 ], wheat [ 42 ], and other crops, as well as increase the rate of seed germination under drought conditions. A number of other laboratory examples are provided in the review article [ 43 ].…”
Section: Discussionmentioning
confidence: 99%